MIF -173G/C (rs755622) polymorphism modulates coronary artery disease risk: evidence from a systematic meta-analysis - Li, De-Yang (BMC Cardiovasc Disord, 2020)
BACKGROUND: Coronary artery disease (CAD) remains one of the major causes of death in humans. Genetic testing may allow early detection and prevention of this disease. This study aimed to investigate the association between the macrophage migration inhibitory factor (MIF) -173G/C (rs755622) polymorphism and susceptibility to CAD based on a meta-analysis. METHODS: We searched several databases to identify observational case-control studies investigating the association between the MIF -173G > C (rs755622) polymorphism and CAD risk published before July 30, 2019. Data were analyzed using the STATA software. RESULTS: Six studies, comprising a total of 1172 CAD cases and 1564 controls evaluated for MIF polymorphisms, were included. The occurrence of CAD was found to be associated with the C allele of the MIF rs755622 SNP in the total population (C/G, OR = 1.489, 95% CI = 1.223–1.813). Further, MIF –173G/C polymorphism was significantly associated with CAD under the allelic model in the Asian (C/G, OR = 1.775, 95% CI = 1.365–2.309) and Caucasian (C/G, OR = 1.288, 95% CI 1.003–1.654) subgroups. The data showed that the risk of CAD was higher in the population carrying the C allele. CONCLUSIONS: We found evidence of associations between MIF -173C/G and CAD susceptibility in the Asian and Caucasian populations.